A difference of absolute value based timing metric for timing synchronization in OFDM system - Das, Anuja; Mohanty, Biswajit; Sahu, Benudhar (International Journal of Engineering and Technology, 2018)
Traditional time synchronization schemes are based on autocorrelation between identical parts of the reference OFDM symbol. However, the time metric of the traditional schemes have a plateau or significant quantity of side lobe. This results in a poor timing synchronization performance. In this paper we are proposing a modified timing metric based on difference of absolute value as a normalized factor. The timing synchronization based on the modified timing metric reduces side lobe and improves the timing synchronization performance.Â Â